Prevention of Typhoid by Vi Conjugate Vaccine and Achievable Improvements in Household Water, Sanitation, and Hygiene: Evidence From a Cluster-Randomized Trial in Dhaka, Bangladesh. (12th April 2022) - Tadesse, Birkneh Tilahun; Khanam, Farhana; Ahmmed, Faisal; Im, Justin; Islam, Md Taufiqul; Kim, Deok Ryun; Kang, Sophie S Y; Liu, Xinxue; Chowdhury, Fahima; Ahmed, Tasnuva; Binte Aziz, Asma; Hoque, Masuma; et al.
Abstract: Background: Typhoid fever contributes to approximately 135 000 deaths annually. Achievable improvements in household water, sanitation, and hygiene (WASH) combined with vaccination using typhoid conjugate vaccines (TCVs) may be an effective preventive strategy. However, little is known about how improved WASH and vaccination interact to lower the risk of typhoid. Methods: A total of 61 654 urban Bangladeshi children aged 9 months to <16 years, residing in 150 clusters with a baseline population of 205 760 residents, were randomized 1:1 by cluster to Vi-tetanus toxoid TCV or Japanese encephalitis (JE) vaccine. Surveillance for blood culture–confirmed typhoid fever was conducted over 2 years. Existing household WASH status was assessed at baseline as Better or Not Better using previously validated criteria. The reduction in typhoid risk among all residents associated with living in TCV clusters, Better WASH households, or both was evaluated using mixed-effects Poisson regression models. Results: The adjusted reduced risk of typhoid among all residents living in the clusters assigned to TCV was 55% (95% confidence interval [CI], 43%–65%; P < .001), and that of living in Better WASH households, regardless of cluster, was 37% (95% CI, 24%–48%; P < .001). The highest risk of typhoid was observed in persons living in households with Not Better WASH in the JE clusters. In comparison with these persons, those living in households with Better WASH in the TCV clusters had an adjusted reduced risk of 71% (95% CI, 59%–80%; P < .001). Conclusions: Implementation of TCV programs combined with achievable and culturally acceptable household WASH practices were independently associated with a significant reduction in typhoid risk. Clinical Trials Registration: ISRCTN11643110. Abstract : Better preexisting household water, sanitation, and hygiene and delivering Vi-TT vaccine act independently to reduce typhoid risk, so that the combination of both yields greater protection against typhoid at the population level (71%) than either vaccination (55%) or improved WASH alone (37%).